DEPRIVING SILKWORMS OF COCOONS: THE TAX SALE (Third Sector Social Economic Review, 2023)
The tax sale repossesses many American homes. The study examines how the tax sale and property tax debt causes taxpayers to lose their houses. Tax sale has not been studied in the national academic literature. In international academic literature, privatization of the taxation process is explored alongside historical examples of tax farming. Secondly, the performance of the private and governmental sectors taxation is compared to the mainstream notion of efficiency. Fundamentally, the article contends these two perspectives are insufficient to comprehend the issue of privatization of the taxation process. The tax sale is only explicable in the context of its role in the process of capital accumulation. In this perspective, the tax sale has been addressed at various stages of capital accumulation in the United States. In addition, the study addressed the tax sales procedure in the context of the taxing power. The study concludes that the tax sale is a reflection of the crisis caused by the capital accumulation process on state finances, that the tax payer inability to pay real estate tax delinquency via the tax sale has become an investment tool for the private sector. Thus, the private sector obtains a portion of the taxing power.Key Words: Capital accumulation process, property tax, tax sale, privatization of tax administration, foreclosure.
Keywords: Capital accumulation process; property tax; tax sale; privatization of tax administration; foreclosure.